Effect of Cognitive Behavioral Therapy (CBT) Based Intervention on Resilience and Burnout among Staff Nurses Working in Critical Care Departments - Khalida Yasmin, Adnan Yaqoob, Hajra Sarwer, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to evaluate the effect of cognitive behavioral therapy (CBT) based intervention on resilience and burnout variables among staff nurses working in critical care department of the healthcare setting. Background: In the healthcare setting, emergency department is extremely risky unit where atmosphere frequently becomes unpredictable. In this environment emergency staff nurses most of the time taking persistent stress effect on mental well-being which lead to exhaustion. In critical care department’s nurses have potentially affected by anxiety due to stressful environment and workload which is the leading factor of negative outcome and result in burnout. Cognitive behavior therapy-based intervention (CBT) is one of the effective intervention to decrease self-reported burnout, as well as increased resilience Methods: A convenient sampling technique was performed collecting the demographic data and information during the face to face interview of 50 working nurse’s staff. The educational interventions, consisted of 08 manualized weekly 60-minute sessions. Data were collected at baseline and after intervention that measured stress, depressive symptoms, anxiety, healthy lifestyle beliefs and behaviors, and job satisfaction. Simple descriptive, paired sample T-test and Wilcoxon signed Rank test was applied for data analysis. Results: The intervention group scored significantly better with moderate to large positive effects on the burnout and resilience variables as well as healthy lifestyle behaviors after the 08 weeks of interventional sessions. Conclusions: The CBT including direct educational sessions has excellent potential as evidence-based interventions for improving the mental health, healthy lifestyle beliefs and behaviors related to job satisfaction in working staff nurses of emergency department.